THE ROLE OF PERCEIVED HEALTH BENEFIT, BRAND IMAGE, AND DESIGN APPEAL TOWARDS HEALTH MASK REPURCHASE INTENTIONS AFTER EASING POLICY OF HEALTH PROTOCOL - Achmadi, Caesar Rosyad; Makarim, Muhammad Harfiansyah; Muzammil, Oktafalia Marisa (Universitas Negeri Yogyakarta, 2024)
This research entitled